Influences of modulation period on structure and properties of AlTiSiN/AlCrSiN nanocomposite multilayer coatings. (November 2021) - Liu, Y.; Liu, H.D.; Pelenovich, Vasiliy; Wan, Q.; Guo, J.L.; Chen, Y.M.; Zhang, J.; Xue, L.J.; Li, Z.G.; Yang, B.
Abstract: Fabricating a multilayer structure with different modulation periods (Λ) is an attractive approach to adjust the properties of the monolithic coatings. Here, multi-layered AlTiSiN/AlCrSiN coatings with Λ ranging from 25 to 147 nm were prepared by the arc ion plating technique. The effects of Λ on the structure and properties of the coatings were investigated systematically. Results showed that all the coatings had a mixed-phase structure consisting of TiN and CrN in rock salt structure and AlN in wurtzite structure. The coating at Λ = 60 nm displayed the optimized hardness and elastic modulus, corresponding to 31.6 GPa and 514 GPa, and the coating at Λ = 25 nm possessed the highest adhesion strength with Lc1  = 41.5 N, Lc2  = 80.2 N, and CPRS  = 1606.1 N 2 . The tribological test showed that the AlTiSiN/AlCrSiN coatings exhibited abrasive wear behavior and the coating at Λ = 25 nm demonstrated the lowest COF of 0.26 and the minimum wear rate of 8.3 × 10 −7 mm 3 /Nm. Highlights: AlTiSiN/AlCrSiN multilayer coatings with various modulation period ranging from 25 to 147 nm were prepared by arc ion plating. Properties of the AlTiSiN/AlCrSiN coatings were significantly affected by the modulation period. The coating with Λ = 60 nm displayed the maximum hardness of 31.6 Gpa and elastic modulus of 514 GPa. The coating with Λ = 25 nm demonstrated the highest adhesion strength of and the best wear resistance.